2018
DOI: 10.4143/crt.2017.296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors Influencing Dental Developmental Disturbances in Childhood Cancer Survivors

Abstract: PurposeAlthough studies regarding dental developmental disturbances after childhood cancer treatment have increased, they have many limitations. Studies analyzing the significance of independent clinical risk factors with regard to the dental health status are also rare. We aimed to investigate the risk factors for dental developmental disturbances, particularly severe disturbances, in childhood cancer survivors (CCS).Materials and MethodsOral examinations and retrospective reviews of medical and panoramic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
71
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(102 citation statements)
references
References 19 publications
(26 reference statements)
16
71
4
3
Order By: Relevance
“…Most of the previous studies indicated that children subjected to H&N and TBI radiotherapy experienced more dental defects compared to children subjected to chemotherapy alone. 14,18,20,27 In a study by Näsman et al, 14 it was found that children treated with radiotherapy developed more dental defects as compared to children treated with multiagent chemotherapy. In another study, severe root defects presented in 9 out of 10 patients that received fractionated TBI, as compared to patients receiving chemotherapy alone who did not develop any late defects.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies indicated that children subjected to H&N and TBI radiotherapy experienced more dental defects compared to children subjected to chemotherapy alone. 14,18,20,27 In a study by Näsman et al, 14 it was found that children treated with radiotherapy developed more dental defects as compared to children treated with multiagent chemotherapy. In another study, severe root defects presented in 9 out of 10 patients that received fractionated TBI, as compared to patients receiving chemotherapy alone who did not develop any late defects.…”
Section: Discussionmentioning
confidence: 99%
“…DeI or Modified Dental Defect Index (MDDI) was often used in previous studies, and it gave some information about the degree of damage to dental development [4,10,11,14]. However, the latency period was not always appropriate to show all of the post-treatment disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there is research undertaken one year after therapy completion [14]. Gawade et al [7,11] suggest a mini-mum two-year follow-up after finishing the anticancer treatment. Cubukcu et al [4] also used DeI to determine the total injury to permanent teeth, but they controlled the subjects in remission at least for five years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations